Analisis Tindak Tutur dalam Video Orasi Aksi Cabut UU Cipta Kerja Omnibus Law di Samarinda - Khotimah, Khusnul; Hudiyono, Yusak; Rijal, Syamsul (Adjektiva: Educational Languages and Literature Studies, 2018)
This study is to describe the form of speech acts, the function of speech acts, and the effects of perlocutionary speech acts that appear in the oration activity of revoking the Omnibus Law Job Creation Act in Samarinda. This study uses the referential method, which is a method where the determinant is in the form of a reference or reality designated by language. The next method is the pragmatic matching method, the determining method is the speech partner. The results of the analysis of locutionary, illocutionary, and perlocutionary speech acts in the oration of the revoking of the Omnibus Law Job Creation Act in Samarinda showed that the speech contained a locutionary speech act in the form of a statement. Locutionary speech acts also found illocutionary speech acts with the types of assertive illocutionary, directive illocutionary, expressive illocutionary, and commissive illocutionary speech acts. The illocutionary speech act is firm with the function of blaming and complaining. Directive illocutionary speech acts with a commanding function. Expressive illocutionary speech acts with the function of thanking and blaming. Commissive illocutionary speech acts with credit function. In this study also found perlocutionary speech acts with the function of influencing other people or certain parties to do something as expected by the speaker, so that there is an effect on the interlocutor. The effect of the perlocutionary speech act that occurs can be seen from the response of the interlocutor by paying attention to the speech context.